Pengaruh Kepemilikan Keluarga dan kepemilikan Institusional terhadap Kinerja Perusahaan di Sektor Perdagangan, Jasa, dan Investasi - Oky Jeania Nellanda; Rahman Anshari; Yulia Tri Kusumawati (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to examine the effect of family ownership and institutional ownership on company performance. The population used in this study were companies included in the trade, services and investment sectors listed on the Indonesia Stock Exchange during the period 2021 to 2023. Through the purposive sampling method, 631 companies were obtained that met the requirements, namely publishing annual reports and sustainability reports and financial reports in rupiah currency during that period. After removing 441 outlier data from the total sample, the final number of companies used in the analysis was 138. The analysis technique applied in this study was multiple linear regression. Based on the results of hypothesis testing, it is known that family ownership and institutional ownership have a negative effect on company performance